Registration of Nutraceuticals and Reporting Adverse Events of Dietary Supplements in USA - BR, NAVYA; GS, Shanthakumar; P, Shrikanth; Agrawal, Ayushi; Ali, Shoukat (Journal of Biomedical and Pharmaceutical Research, 2020)
The US FDA characterizes Nutraceuticals as "Dietary Supplements" Under DSHEA (Dietary Supplement Health Education Act-1994). In USA Food and Drug Administration (FDA) controls nutraceutical under different guidelines. According to DSHEA producer should make sure that nutraceutical is safe before it is promoted. The FDA concentrating on quality and safety of the product as these are used by humans. As food items are coming to starting with one nation then onto the next, keeping up safety and quality principles according to different regulatory frameworks set by the individual governments gets significant.